2017
DOI: 10.1038/leu.2017.213
|View full text |Cite
|
Sign up to set email alerts
|

The MLL recombinome of acute leukemias in 2017

Abstract: Chromosomal rearrangements of the human MLL/KMT2A gene are associated with infant, pediatric, adult and therapy-induced acute leukemias. Here we present the data obtained from 2345 acute leukemia patients. Genomic breakpoints within the MLL gene and the involved translocation partner genes (TPGs) were determined and 11 novel TPGs were identified. Thus, a total of 135 different MLL rearrangements have been identified so far, of which 94 TPGs are now characterized at the molecular level. In all, 35 out of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
616
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(662 citation statements)
references
References 68 publications
15
616
0
16
Order By: Relevance
“…The fusion of TET1 and MLL has been reported in a number of AML/ALL [24, 25, 31-33]. A recent study indicates that TET1 has essential oncogenic function in the development of MLL-rearranged leukemia, which is through coordination with MLL-fusion proteins in regulating their critical co-targets including homeobox A9 (Hoxa9), myeloid ecotropic viral integration 1 (Meis1), and pre-B-cell leukemia homeobox 3 (Pbx3) genes [19, 78].…”
Section: Tet1 In Human Hematologic Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion of TET1 and MLL has been reported in a number of AML/ALL [24, 25, 31-33]. A recent study indicates that TET1 has essential oncogenic function in the development of MLL-rearranged leukemia, which is through coordination with MLL-fusion proteins in regulating their critical co-targets including homeobox A9 (Hoxa9), myeloid ecotropic viral integration 1 (Meis1), and pre-B-cell leukemia homeobox 3 (Pbx3) genes [19, 78].…”
Section: Tet1 In Human Hematologic Malignanciesmentioning
confidence: 99%
“…In the process of demethylating DNA, TET enzymes further practice 5-hmC to generate 5-fC and 5-caC, both of which can be removed by thymine DNA glycosylase by base excision repair (BER) [22, 23, 30]. In the history of TET proteins, researches demonstrated that fusion of the N-terminal region of MLL H3K4 methyltransferase with the DSBH domain of TET1 is related with acute myeloid/lymphoid leukemias [24, 25, 31-33]. TET2 mutations correlate with many hematologic malignancies, such as myelodysplastic syndromes (MDS), myeloproliferative neoplasms (MPN), CMML, AML, secondary AML, and so on [34-42].…”
Section: Introductionmentioning
confidence: 99%
“…9 The most common rearrangements are balanced chromosomal translocations that fuse the N-terminus of the MLL gene in frame with the C terminus of .130 different partners, producing oncogenic MLL-fusion proteins (MLL-FPs). 10,11 Although the exact molecular mechanism of most fusions remains unknown, MLL-FPs mediate aberrant recruitment of transcription machinery to MLL target genes, driving overexpression of HOX genes (eg, HOXA9) and other coregulators such as MEIS1 and PBX3. [12][13][14] The extreme N-terminus of MLL forms a triple complex with MENIN and lens epithelium-derived growth factor/p75 (LEDGF/p75), a prerequisite for targeting the MLL oncogenic complex to target genes ( Figure 1A-B).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with complex karyotypes (CKs), defined as those with multiple chromosomal abnormalities, have a dismal outcome [Mrózek, 2008]. However, the prognosis for leukemias with a KMT2A rearrangement ( KMT2A -r), representing 18% of childhood leukemias, which may be accompanied by multiple chromosomal changes, appears to depend on the fusion partner gene [Meyer et al, 2018]. Thus, a precise characterization of KMT2A -r and the fusion partner genes, especially in CKs, is of interest for managing AML [Daser and Rabbitts, 2004;Pui et al, 2011;Marschalek, 2015;Ney Garcia et al, 2016].…”
mentioning
confidence: 99%
“…In the context of KMT2A -r involving genes in the 19p13 region, 2 partner genes have been repeatedly identified. KMT2A may be fused to MLLT1 (also called ENL [elongation factor for RNA polymerase II]); this fusion is common in KMT2A-r-positive infant acute lymphoblastic leukemia but is found in less than 1% of pediatric KMTA2 -r-positive AML cases [Meyer et al, 2018]. Alternatively, KMT2A may fuse with the ELL gene (11-19 lysine-rich leukemia gene) in the 19p13.1 chromosomal region.…”
mentioning
confidence: 99%